HUBUNGAN TINGKAT PENDIDIKAN DENGAN PENGETAHUAN TENTANG INFEKSI SOIL TRANSMITTED HELMINTHS PADA IBU PENGAJIAN RANTING AISYIYAH KECAMATAN MEDAN DENAI - ANGGIE YURIKO; NELLI MURLINA (JURNAL ILMIAH KOHESI, 2023)
Soil Transmitted Helminths (STH) is one of the most common infections worldwide. According to the World Health Organization (WHO) 24% of the world's population, are infected with STH. The impact of STH infection is decrease in children's cognitive abilities and achievement. The low education level is the high main cause of STH. To determine the relationship between education level and knowledge of STH in mothers of aisyiyah. Analytical descriptive research method with a cross sectional approach. Data collection using categorical analytic formulas will then be carried out by the Chi-square analysis test. The level of knowledge of respondents is based on the latest level of education at Junior High School was 2 people (6.7%) with a low level of knowledge, the last level of education at Senior High School had a good level of knowledge as much as 2 people (5.27%), the level of knowledge was sufficient as much 9 people (32.75%), and the level of lack of knowledge was 2 people (5.27%), and at the last education level D3 / Bachelor degree where 4 people had a good level of knowledge (14.45%), and the level of knowledge was sufficient 11 people (35.55%). The Chi-Square test results obtained p value = 0.004 (p <0.05). There is a relationship between education level and knowledge level.